Analisa Faktor Yang Berhubungan Dengan Kecemasan Ibu di Ruang Nicu dan Nhcudi di Rumah Sakit Panti Rapih Yogyakarta - Wulandari Tutik Priyani, Rosa; Mahayanti, Agnes; Ririn Widianti, Christina (I Care Jurnal Keperawatan STIKes Panti Rapih, 2021)
ABSTRACT Background: Hospitalization is the entry of individuals into the hospital as a patient to get help in medical care or treatment. Intensive care for neonates who are treated in the NICU or NHCU will cause anxiety and worry for the baby's mother. Anxiety is a vague fear accompanied by feelings of uncertainty and discomfort. Anxiety response is the most common thing experienced by mothers when there are health problems in their babies. Objective: The purpose of this study was to determine the factors associated with maternal anxiety in the NICU and NHCU rooms at Panti Rapih Hospital, Yogyakarta. Methods: This study uses a quantitative, analytic survey design with a cross sectional approach. The population in this study were all mothers who had babies who were treated in the NICU and NHCU rooms at Panti Rapih Hospital, Yogyakarta. Sample of 35 respondents was obtained by accidental sampling technique. The research instrument used is a questionnaire. Results: There was a significant relationship between age (p-value: 0.039), education (p-value: 0.028), occupation (p-value: 0.010), economic status (p-value: 0.003), length of stay (p-value : 0.015), and there is no significant relationship between the environment and maternal anxiety (p-value: 0.551). Conclusion: The factors that were related to the anxiety of mothers in the NICU and NHCU rooms at Panti Rapih Hospital Yogyakarta were age, education, occupation, economic status and length of stay. The unrelated factor is the environment. Suggestions for NICU and NHCU nurses are expected to increase education about the condition of the baby to the baby's mother and teach the mother in caring for her baby.